Long-term Chemical Fertilization Impacts on Kinetics of K Release, Wheat Yield, and K Uptake in a Typic Ustrochrept Soil of Punjab, India. Issue 1 (2nd January 2016) - Brar, B. S.; Romana, P. S.; Saini, S. P.
ABSTRACT: Long-term experiments are leading indicators of sustainability and serve as an early warning system to detect problems that threaten future productivity. An increasing trend in yield is necessary for a system to be called sustainable. Impact of long-term use of inorganic fertilizers on kinetics of K release, wheat (Triticumaestivum L) yield, and K uptake in a sandy loam, typicustrochrept soil was studied under maize (Zea mays L)-wheat cropping sequence. Potassium release was higher in K-treated soil than in K-minus soil. Potassium released from clay fractions after 264 h was 3.1 and 6.2 m mole kg −1 for without-K (soil I) and with-K fertilization (soil II), respectively. The amount of K released from silt fractions was 2.1 and 3.4 m mole kg −1 for soil I and soil II, respectively. Lowest amount of K release was recorded in a sand fraction which was 1.1 and 2.1 m mole kg −1 for soil I and soil II, respectively. Elovich equation fit well and explained the nonexchangeable K release in these soils. Higher rate constant values were observed in soil receiving K fertilizer as compared with without-K application. Grain yield of wheat increased significantly with the increase in K from 0 to 41 and 82 kg K ha −1 . The K uptake was higher than the K applied to wheat indicating that nonexchangeable K contributed toward its uptake in wheat crop. The application of K helps to reduce the mining of K from nonexchangeable form, which results in yield increase in wheat.